PENGARUH BERBAGAI MEDIA TERHADAP SUHU MEDIA DAN PRODUKSI MAGGOT - Nugrahani, Irene Laksmi; Fathul, Farida; Tantalo, Syahrio (Jurnal Riset dan Inovasi Peternakan, 2018)
This study aimed to determine the effect of various growth media to the media maggot temperatures and maggot production.  Apart from that for know about the relationship between of media pH and media temperature. The research was conducted on May 3-June 12, 2017 in the Cage Department of Animal Husbandry and Lampung State Polytechnic Analysis Laboratory. This study uses a completely randomized design (CRD) with four treatments and five replicates media. Treatments of media include: R1 (tofu waste), R2 (palm kernel meal), R3 (fish waste) and R4 (chicken blood). The research data were analyzed variance at 5% or 1%, and a further test by Duncan test. Moreover, it also tested the relation between C/N ratio maggot media and production, as well as media temperature and pH testing media with orthogonal polynomials.  The results showed a highly significant difference in various media to the media on the morning temperature (P <0.01).  On the contrary, the influence of various media on the temperature during the day and evening was not significantly different (P> 0.05). The highest maggot production on palm kernel mealmedia with an average of 358.5 ± 65.76 gram.  The relationship between the temperature of the chicken blood media and media pH was very tight with the equation Ŷ=-47.00+2.00X, [26.0: 26.50ᴼC] and r=1. Keywords: maggot, media, temperature, pH